Problems at around Achaemenid Royal Road between Susa and Persepolis: Routes and Stations - Velázquez Muñoz, Joaquín (Gerión. Revista de Historia Antigua, 2013)
In this paper I analyze the existing problems in establishing the rout followed by the Achaemenid Royal Road between Susa and Persepolis, well as the location of the stations mentioned in the Persepolis Fortification Archive that were located on this important route. While the itinerary of the Royal Road can be reconstructed from the study of ancient sources and archaeology, the localization of the stations on a map raises many doubts. A lot of hypotheses and patterns are proposed for the analysis of Fortification Archive texts that, along with subsequent archaeological and toponymic investigations, will allow us to have a better understanding of the location of the stations and their distribution in the different routes followed by the Achaemenid Royal Road in Fārs.
Keywords: Royal Road; Route; Station; Seal; Fortification Archive.